PENERAPAN NOTE MAKING SKILL UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS FKIP UMSU - Halimah Tussa'diah (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to improve the listening skill of the second semester students Prodi English Education of FKIP UMSU by applying note making skills, and determine the extent of the increase in students learning outcomes in subjects Listening II after appliying Note making Skill. This research was conducted by using the method of Class Action Research (Class Action Research), and the result were analyzed by using descriptive quantitative and qualitative method to explain the observation of activities. The subjects were the students of the second semester, the class IIC-2, Prodi FKIP UMSU English Education, Academic year 2014/2015, totaling 33 people. The result showed that: (1) The abilty of students to record verbal information needed appropriately increase. This is eviden from the increase in value of the average students 58.64 in pre-test I cycle I, being 74.70 in the post-test II, the second cycle with standart KKM = 70 (2) the result of the students’ learning showed a significant increase, which gained 100 % completeness study fulfilled within two cycles. This improvement can also be seen from was the increase in the percentage mastery learning from 30.30% in pre test I cycle I, being 60,61% in post test I cycle II, and 100% in post test II cycle II with the standart learning completeness = 80% students passed.